Daily Incision Cleansing with Alcohol Reduces the Rate of Surgical Site Infections: A Pilot Study. Issue 11 (November 2015) - Vogt, Kelly N.; Chadi, Sami; Parry, Neil; Gray, Daryl; Brackstone, Muriel
Surgical site infections (SSIs) represent a significant source of preventable patient morbidity and hospital expense. Our objective was to assess the role of postoperative incisional alcohol cleansing in decreasing the rates of SSI as compared with standard care (control). Patients undergoing clean-contaminated abdominal operations at a single center were included. Prospectively collected data on control patients were compared with patients treated with daily postoperative alcohol-based surgical site cleansing (70% isopropyl alcohol) for the primary outcome of an SSI within the first 30 postoperative days. A total of 93 patients were included, 56 managed with standard care and 37 managed with the addition of daily alcohol cleansing. A significantly lower rate of SSI in the group managed with daily alcohol cleansing was observed (13% vs 32%, P = 0.04). This study suggests a role for adding daily incisional alcohol cleansing to further reduce the rate of SSIs.